Dual-functional liposomes for curcumin delivery and accelerating silk fibroin hydrogel formation - Laomeephol, Chavee (2020)
The administration of a drug-loaded implantable hydrogel at the tumor site after surgical resection is a viable approach to prevent the local recurrence or metastasis. Dimyristoyl glycerophosphorylglycerol (DMPG)-based liposomes were developed for inducing the rapid gelation of silk fibroin (SF) and delivering an anticancer drug, curcumin. Curcumin was loaded in the liposomes and the stability of curcumin was enhanced. The gelation time of liposome-induced SF hydrogels ranged from 3 min to more than 6 h. The biological activity of liposome-SFhydrogels was evaluated in vitro using L929 fibroblasts and MDA-MB-231 breast cancer cells. The release of curcumin can inhibit the growth of cancer cells. Both cells cultured on the surface of the hydrogels loaded with curcumin displayed low cell survival due to the combination of low cell attachment and cytotoxicity of curcumin. Liposome-SF hydrogels show potential as a sealant administered at the tumor site to eliminate residual cancer cells after tumor removal.